Pengembangan Modul Bahan Ajar Berbasis Website Untuk Meningkatkan Hasil Belajar pada Materi Mekanisme Pasar - Novitasari, Anindita Trinura; Pratikto, Heri; Rahayu, Wening Patmi (Research and Development Journal of Education, 2024)
Teaching material modules as a means of supporting teaching and learning activities for students are a source of learning materials that can improve student learning outcomes. Designed systematically to help the process of understanding the topics discussed in a learning material. The teaching material module has evolved into it earier for students and educators to have flexibility in adequate accessibility anywhere and anytime in a learning contaxt that is not limited to just being in the classroom face to face. The design is effective, such as attention to students learning needs, multimedia-based, combining text, images, video and animation to be more interactive and interesting. The validity test of the website-based teaching material module showed very feasible test results through assessments by media experts, material experts, and trials on students. The learning results obtained from using that the cognitive level of students on the topic of discussion material in this module has increased through a better level of learning outcomes in the average class value compared to conventional modules.